Pengaruh Persaingan Usaha Tidak Sehat terhadap Kepuasan dan Kepercayaan Konsumen dalam Kondisi Pandemi Covid-19 - Verda Raseindriyasari Bidjaksono; Teddy Prima Anggriawan; Aldira Mara Ditta Caesar Purwanto (Pusat Riset dan Inovasi Nasional, 2023)
The negative impact of the Covid-19 pandemic has caused problems with the protection of consumer rights. This happens when their access to basic goods and services is poor as a result of unfair economic practices and causes unfair business competition. In Law No.8 of 1999 concerning Consumer Protection Article 4 which regulates consumer rights. During the Covid-19 pandemic, it has caused various impacts that go hand in hand with the era of disruption, causing consumers to be in a weak position. In dealing with the Covid-19 pandemic case, it is not only regulated by national legislation or legislation, but also by human rights law, especially those that have been officially recognized by the state. These activities have implications for the implementation of business competition supervision carried out by the Business Competition Supervisory Commission (KPPU).